Evaluation of Collagen Triple Helix Repeat Containing-1 protein in Postmenopausal Women with Osteoporosis - Salman , Isam; Mohammed, Noor Ulhuda; Abd Al-Ghanny, Rand Jalal; Abed, Baydaa; mutar , Samara (AL-Kindy College Medical Journal, 2024)
Background: The collagen triple helix repeat containing 1 (CTHRC1) protein has been connected to decreased levels of vitamin D and calcium, as well as obesity. This study aimed to investigate the relationship between CTHRC1 and osteoporosis in post-menopausal women and compare with healthy subjects.Subjects and Methods: A cross-sectional study consisted of 86 women were enrolled in this study and divided into three groups based on the results of dual-energy densitometry (DXA): 30 women with osteoporosis, 30 women with osteopenia, and 26 healthy women. Data on demographic and clinical features and laboratory values of Calcium (Ca) and Vitamin D3 (V.D3) were recorded.Results: Women with osteoporosis had significantly increased levels of CTHRC1 (P = 0.0001) compare to HS groups. The CTHRC1 showed negative correlation with Ca and V.D3 value at (r= -0.453, P=0.001 and r= -0.415, P= 0.022) respectively in osteopenia patients. CTHRC1 alone show excellent discrimination power (AUC= 0.9) in identifying women with osteoporosis.Conclusions: Serum CTHRC1 is a valid biomarker that can distinguish women with osteoporosis from HS group with high accuracy. Low calcium and vitamin D levels in this age group may be linked to an increase in the CTHRC1 levels and this could make it a Therapeutic target in future studies.